Rhinovirus Infection Induces Expression of Its Own Receptor Intercellular Adhesion Molecule 1 (ICAM-1) via Increased NF-κB-mediated Transcription - Papi, Alberto; Johnston, Sebastian L. (The Journal of biological chemistry, 1999)
Virus infections, the majority of which are rhinovirus infections, are the major cause of asthma exacerbations. Treatment is unsatisfactory, and the pathogenesis unclear. Lower airway lymphocyte and eosinophil recruitment and activation are strongly implicated, but the mechanisms regulating these processes are unknown. Intercellular adhesion molecule-1 (ICAM-1) has a central role in inflammatory cell recruitment to the airways in asthma and is the cellular receptor for 90% of rhinoviruses. We hypothesized that rhinovirus infection of lower airway epithelium might induce ICAM-1 expression, promoting both inflammatory cell infiltration and rhinovirus infection. We therefore investigated the effect of rhinovirus infection on respiratory epithelial cell ICAM-1 expression and regulation to identify new targets for treatment of virus-induced asthma exacerbations. We observed that rhinovirus infection of primary bronchial epithelial cells and the A549 respiratory epithelial cell line increased ICAM-1 cell surface expression over 12- and 3-fold respectively. We then investigated the mechanisms of this induction in A549 cells and observed rhinovirus- induction of ICAM-1 promoter activity and ICAM-1 mRNA transcription. Rhinovirus induction of ICAM-1 promoter activity was critically dependent upon up-regulation of NF- Kappa B proteins binding to the -187/-178 NF- Kappa B binding site on the ICAM-1 promoter. The principal components of the rhinovirus-induced binding proteins were NF- Kappa B p65 homo- or heterodimers. These studies identify ICAM-1 and NF- Kappa B as new targets for the development of therapeutic interventions for virus-induced asthma exacerbations.